APPLICATION OF AUTOMATIC RECORDER AND SOUND ANALYSIS IN SURVEYING THE PRESENCE AND DISTRIBUTION OF BIRD SPECIES IN NGOC LINH NATURE RESERVE, QUANG NAM PROVINCE - Tien Thinh, Vu; Thi Dinh, Le; Van Dung, Tran; Thi Hoa, Nguyen; Chi Thanh, Nguyen; Thanh Hai, Dong; Dac Manh, Nguyen; Trong Toan, Giang; Huu Van, Nguyen; A Tung, Thao (Journal of Forestry Science and Technology, 2017)
It is necessary to have accurate information on a species' presence and distribution in order to monitor and protect an endangered species. While traditional survey methods have a several limitations, using automatic recorders in monitoring wildlife provides significant promise for detecting bird species. In this study we examined the application of automatic recorders and the associated sound analysis software (RAVEN software) to survey for the presence of 21 bird species. The survey was conducted at 11 study sites in three communes in Ngoc Linh Nature Reserve, Quang Nam province in June and July of 2016. The recordings and subsequent analysis detected the sounds of 9 bird species out of the total of 21 targeted bird species. The different species identified were detected with varying levels of frequency. While some species were detected many times in a recording and in various recordings, the others only appeared a few times in all recordings. Their active time during sampling period (3.00 - 9.00 AM) varied by species.